Utopian pasts and futures in the contemporary American novel - Lanzendörfer, Tim (Edinburgh University Press, 2024)
"Utopian Pasts and Futures in the Contemporary American Novel highlights the emergence of a literary mode, speculative historism, over the past two decades in U.S. literature. Discussing in depth novels by writers such as Ken Kalfus, Joyce Carol Oates, and Colson Whitehead, among others, it integrates questions of critical method, genre, form, and literary theory, all of which have some urgency today. Addressing itself to the question of how to read this mode through a form of utopian hermeneutics, this study explores the formal constitution, narrative choices, and place in the wider literary market of a mode that it believes to be constitutively important for understanding American literature's struggle with the possibility of imagining hopeful futures"--